UPICC SEBAGAI MODEL BAGI PEMBARUAN HUKUM KONTRAK INDONESIA DALAM RANGKA MENGANTISIPASI BERLAKUNYA MASYARAKAT EKONOMI ASEAN TAHUN 2015 - Subianta Mandala (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
The current Indonesian contract law which is inherited from then Dutch colonial is no longger compatible with the the rapid development of international trade and business practice. Indonesia, therefore for quite long time, has made an effort to reform its contract law. However, those efforts are not successful so far. The entry into force of the ASEAN Economic Community in 2015 is a good momentum for Indonesia to revisit the idea of the reform. This research tried to find out the most possible approach for the reform. The research applied normative juridical method with futuristic approach. In conclusion, UPICC as an international instrument may well serve as model for the new Indonesian contract law. With its soft law character, UPICC may flexibly be adjusted in order not to prejudice the fundamental principles of Pancasila.